2019
DOI: 10.1080/14656566.2019.1594772
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging osteoporosis pharmacotherapy for women: state of the art therapies for preventing bone loss

Abstract: Introduction: Pharmacological options to address the imbalance between bone resorption and accrual in osteoporosis include anti-resorptive and osteoanabolic agents. Unique biologic pathways such as Wnt/-catenin pathway have been targeted in the quest for new emerging therapeutic strategies. Areas Covered: This review aims to provide an overview of existing pharmacotherapy for osteoporosis in women and explore state-of-the-art and emerging therapies to prevent bone loss, with an emphasis on the mechanism of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“…In another study, lower levels of Dialister, Enterobacter, Escherichia-Shigella, Fecalibacterium, and Kluyvera but higher levels of Veillonella, Bacteroides, and Fusobacterium compared to that of the controls were found . The correlations between the relative abundance of the above-mentioned bacterial genera and systemic inflammation-related markers including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), prognostic nutritional index (Fontalis et al, 2019), and lymphocyte-tomonocyte ratio (LMR) were analyzed. The results showed that Enterobacter and Escherichia-Shigella, were correlated positively with serum NLR level, while Dialister was negatively correlated with contents of PLR and NLR in the serum.…”
Section: Lung Cancermentioning
confidence: 99%
“…In another study, lower levels of Dialister, Enterobacter, Escherichia-Shigella, Fecalibacterium, and Kluyvera but higher levels of Veillonella, Bacteroides, and Fusobacterium compared to that of the controls were found . The correlations between the relative abundance of the above-mentioned bacterial genera and systemic inflammation-related markers including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), prognostic nutritional index (Fontalis et al, 2019), and lymphocyte-tomonocyte ratio (LMR) were analyzed. The results showed that Enterobacter and Escherichia-Shigella, were correlated positively with serum NLR level, while Dialister was negatively correlated with contents of PLR and NLR in the serum.…”
Section: Lung Cancermentioning
confidence: 99%
“…(2,4,5) Osteoporosis medications are particularly effective in reducing the risk of VFs in postmenopausal women, and it is therefore of utmost importance that VFs come to clinical attention. (8,9) Spine imaging is required for the diagnosis of VF and the clinical challenge is to identify and diagnose the asymptomatic two-thirds of individuals with VF, (10) in addition to detect VFs not reported correctly by the radiologist. (11) Vertebral fracture assessment (VFA) is a well-established and validated method for detecting VFs from lateral spine imaging (LSI) with dual-energy X-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bisphosphonates can markedly inhibit bone resorption and are very efficient at reducing osteoclast numbers and activity, while they also profoundly decrease bone formation 22 . Moreover, lasofoxifene belongs to selective estrogen receptor modulators (SERMS) downmodulating the activity of osteoclasts in a transforming growth factor-β3-dependent manner leading to reduced bone resorption 23 , while it is associated with an approximately two fold increased risk of deep vein thrombosis 24 . As a selective IKK-β inhibitor, IMD 0354 downregulates IκB phosphorylation and blocks NF-κB P65 nuclear translocation.…”
Section: Introductionmentioning
confidence: 99%